Language Works 5(1) - Andersen, Elisabeth Muth; Bala, Paulina; Nguyen, Michael Hai; Nielsen, Jessie Leigh; Sørensen, Søren Sandager; Thøgersen, Jacob (Journal of Language Works - Sprogvidenskabeligt Studentertidsskrift, 2020)
Corona pandemic or not, no summer without a new issue of Language Works. With this issue, we present the eighth publication of the journal.